Improving the Acetic Acid Fermentation of Acetobacter pasteurianus by Enhancing the Energy Metabolism - Song, Jia; Wang, Jun; Wang, Xinyu; Zhao, Hang; Hu, Tao; Feng, Zhiwei; Lei, Zhi; Li, Weizhao; Zheng, Yu; Wang, Min (Frontiers in Bioengineering and Biotechnology, 2022)
Energy metabolism is important for cell growth and tolerance against environment stress. In acetic acid fermentation by Acetobacter pasteurianus, the correlation coefficients of acid production rate with energy charge and ATP content were 0.9981 and 0.9826, respectively. The main energy metabolism pathway, including glycolysis pathway, TCA cycle, ethanol oxidation, pentose phosphate pathway, and ATP production, was constructed by transcriptome analysis. The effects of fermentation conditions, including dissolved oxygen, initial acetic acid concentration, and total concentration, on acetic acid fermentation and energy metabolism of A. pasteurianus were analyzed by using the RT-PCR method. The results showed the high energy charge inhibited glucose catabolism, and associated with the high ethanol oxidation rate. Consequently, a virtuous circle of increased ethanol oxidation, increased energy generation, and acetic acid tolerance was important for improving acetic acid fermentation.